Cognitive Behavioral Therapy to Reduce Academic Stress among Nursing Students: A Quasi-Experimental Study - Sustrami, Dya; Susanti, Ari; Ardhy Wahyu Ramadhana Putra; Suhardiningsih, A.V. Sri (Universitas STRADA Indonesia, 2026)
Background: Academic stress was commonly experienced by university students as a result of high academic demands and workload. Cognitive Behaviour Therapy (CBT) is one of the methods that can help individuals identify irrational thought and replace them with adaptive cognitions so they can assess academic situation more realistically and rationally. Purpose: The purpose of this study was to analyze the effectiveness of CBT in reducing academic stress among nursing students. Methods: A quasi-experimental pre–post-test design was applied with 141 participants selected through simple random sampling, consisting of 70 respondents in the experimental group and 71 in the control group. The intervention group received a two-week CBT program based on the ABCDE model and cognitive restructuring techniques. The Student Life Stress Inventory (SSI) was administered before and after the intervention. Data were analyzed using the Wilcoxon Signed Rank Test and Mann–Whitney U Test. All procedures of this study were approved by the Research Ethics Committee of STIKes Hang Tuah Surabaya Number PE/50/II/2025/KEP/SHT Results: The Wilcoxon test showed a significant reduction in stress levels in the experimental group (Z = –3.088, p = 0.002), while no significant difference was found in the control group (Z = –0.765, p = 0.444). The Mann–Whitney U Test revealed a significant difference in post–pre score changes between groups (U = –3.017, p = 0.003), indicating that CBT was effective in decreasing stress levels. Conclusion: CBT effectively reduced academic stress among nursing students.CBT also can be used as an effective non-pharmacological nursing intervention in stress management.